1977
DOI: 10.1007/bf03006808
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular reactions to laryngoscopy and tracheal intubation following small and large intravenous doses of lidocaine

Abstract: The efficacy of intravenously administered lidocaine 0.75 mg/kg and 1.5 mg/kg to protect against cardiovascular reactions associated with laryngoscopy and tracheal intubation was studied in two comparable groups of ten patients and compared with a similar control group of ten patients given only saline. Following laryngoscopy and tracheal intubation, the 1.5 mg/kg dose afforded complete protection against cardiac arrhythmias of all types. The smaller dose was ineffectual in this respect. While the larger dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(12 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…In this study, the effects of intravenous magnesium sulfate on laryngospasm after elective tonsillectomy in children were studied. Magnesium sulfate is also used for curing acute bronchospasm and severe asthma with dose of 10-25 mg/kg in children (11, 12). …”
Section: Discussionmentioning
confidence: 99%
“…In this study, the effects of intravenous magnesium sulfate on laryngospasm after elective tonsillectomy in children were studied. Magnesium sulfate is also used for curing acute bronchospasm and severe asthma with dose of 10-25 mg/kg in children (11, 12). …”
Section: Discussionmentioning
confidence: 99%
“…[11] demonstrated that intravenous lidocaine 1 mg/kg administered two minutes before endotracheal intubation prevented coughing and increased blood pressure and heart rate, during and after extubation. In our study there was a significant increase in heart rate, systolic and diastolic blood pressure at one, two, three, five and ten minutes following extubation, in Group P. Paediatric patients with cleft palate usually have upper respiratory tract infections (URTI) and thus have hyper-reactive airways that precipitate laryngospasm.…”
Section: Discussionmentioning
confidence: 99%
“…[34] In patients with coronary artery disease, leaking abdominal aneurysm, intracranial aneurysm and recent myocardial infarction these transient changes can result in potentially deleterious effects such as myocardial ischemia, left ventricular failure and cerebral hemorrhage. [456]…”
Section: Introductionmentioning
confidence: 99%